FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAN PERBANKAN DI INDONESIA TAHUN 2012-2017 - Iqbal Notoatmojo (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2020)
This study is aimed to analyze and test the increase of company value through tangibility assets, firm size, profitability, liquidity and capital structure. (Study of 22 listed banking companies Go Public and listing on the Indonesia Stock Exchange in 2012-2017).This research is a type of explanatory research. Data collection uses documentary techniques. Data type uses secondary data, namely the banking financial statements which have been published during 2012 until 2017. data analysis using panel data regression analysis test that is the Fixed Effect estimation model, classic assumption test, and hypothesis testing using the Eviews program tool version 10.0. The partial test results show Tangibility Assets, Firm Size, and DER significant affect the firm value, while profitability Liquidity and DAR have no significant effect on the value of banking companies (PBV), while the F test results simultaneously give an effect on the dependent variable with adjusted R2 of 0.875831. Keywords: Tangibility Assets; Firm Size; Profitability; Liquidity; Capital Structure; Price Book Value.